1994
DOI: 10.1159/000292536
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti-CandidaalbcansIgE Antibodies in Vaginal Washes from Patients with Acute Vulvovaginal Candidiasis

Abstract: Vaginal washes from 55 women were investigated by means of an ELISA method for the presence of IgE antibodies against Candidaalbicans. These antibodies were detected in 87.1 % of patients with clinical acute vulvovaginal candidiasis (group I), 100% of patients with suspected vulvovaginal candidiasis but negative by microscopy and culture (group II), 0% of asymptomatic carriers (group III) and 33.3% of uninfected controls (group IV). Statistically significant differences were observed comparing groups I and II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…30 One study has described a higher level of non- C. albicans species occurrence over time. 31 As stated by Ferrazza et al 32 , almost 25% of VVC cases were caused by non- albicans species. Comparing the results of our study with those other studies which demonstrated, C. glabrata to be the second most significant species among VVC cases because of its higher frequency and increased rate of clinical resistance to antifungals.…”
Section: Discussionmentioning
confidence: 91%
“…30 One study has described a higher level of non- C. albicans species occurrence over time. 31 As stated by Ferrazza et al 32 , almost 25% of VVC cases were caused by non- albicans species. Comparing the results of our study with those other studies which demonstrated, C. glabrata to be the second most significant species among VVC cases because of its higher frequency and increased rate of clinical resistance to antifungals.…”
Section: Discussionmentioning
confidence: 91%
“…It appears as white patches known as “plaques” which resemble milk curds. [1315] One way to distinguish candida plaques from milk curds is that if the surface of the plaque is scraped away, a sore and reddened area will be seen underneath, which may sometimes bleed. It occurs most commonly in babies, particularly in the first few weeks of life.…”
Section: Types Of Fungal Infectionsmentioning
confidence: 99%
“…Some studies have demonstrated the IgE presence in serum and vaginal secretions in 87% of women with vaginal candidiasis (Witikin et al, 1988;Regúlez et al, 1994) increasing the premise that the immunoglobulin role in the vaginal candidiasis pathogenesis is associated to the histamine released by locally mast cells. Furthermore, histamine is able to locally induce the prostaglandin E2 production that may be responsible for the local immune response and immunomodulation process (Witikin et al, 1988;Noverr et al, 2001;Regúlez et al, 1994).…”
Section: Discussionmentioning
confidence: 99%